Hubungan Stress Kerja Dengan Turnover Intention Pada Karyawan Perusahaan Pembiayaan PT. FIF Group - Sari, Winda Retno; Supriyati, Supriyati; Purnama, Rahmad (Universitas Islam Negeri Raden Intan Lampung, 2018)
Turnover intention is the intention of leaving an employee from a company and looking for alternatives to other companies or other jobs. Turnover intention is generated on the basis of the workload experienced by employees. This study aims to determine the relationship between work stress and turnover intention on employees. The hypothesis proposed is that there is a positive relationship between work stress and employee turnover intention. The subjects of this study were permanent employees and contracts who worked less and more than one year in the PT. Financing Company. FIF Group Unit II Tulang Bawang. The sample in this study was 60 people. The sampling technique used was a saturated sampling technique. The research data was collected with the Turnover Intention Scale, Job Stress Scale. The Intention Turnover Scale consisted of 49 valid items with a reliability coefficient of 0.956. The Job Stress Scale consisted of 20 valid items with a reliability coefficient of 0.871. Data analysis using Pearson Product Moment Correlation analysis technique, obtained results r = 0.256 with a significant level of 0.048 (p <0.05). This means that there is a positive relationship between work stress and turnover intention on employees. The value of r2 = 0.066 means that in this study work stress only gives a contribution of 6.6% to turnover intention.